Pelatihan Membaca 15 Menit Untuk Menguatkan Program Gerakan Literasi Sekolah (Gls) Peserta Didik di Pulau Pari Kepulauan Seribu Selatan - Irdalisa; Sari, Yessy Yanita; Fitriani, Somariah; Ifani, Nesa Nur (CV Putra Publisher, 2024)
The literacy ability of Indonesian students is still in the low category, this is proven by the learning process so far not yet at the stage of acquiring knowledge, students adapting to students' desires in learning to acquire knowledge. Another thing is that the learning model still lacks the use of learning models in increasing students' literacy to become a habit in students' daily lives. The School Literacy Movement is an educational ecosystem that was formed with efforts to involve students, teachers, school principals, parents and local communities. So a collection of books is needed that integrates material with the surrounding environmental conditions to attract students' attention in reading, so that students' literacy can improve well. The community service methods used are in the form of training, mentoring carried out face-to-face through lectures and practice and distribution of interviews and observations. Participants in this activity were students of SDN Pulau Pari 01 Pagi. Service is carried out in several stages including planning, implementation, evaluation and mentoring. Data collection techniques are carried out through field observations, documentation, interviews and observations. The results obtained showed that students were able to understand reading after carrying out reading training using the reading aloud technique for 15 minutes.